RELEVANSI PRAKTIK MEDITASI TERHADAP STRES DAN KECEMASAN: KAJIAN BERDASARKAN SATIPAṬṬHĀNA SUTTA DAN ĀNĀPĀNASATI SUTTA - Fabiyanti, Neni; Acep, Lauw (STKIP Subang, 2026)
This study is motivated by the rising prevalence of stress and anxiety in modern life and the need for a deeper conceptual approach drawn from Buddhist textual sources. The objective is to explain the relevance of meditation practice to stress and anxiety based on a textual study of the Satipaṭṭhāna Sutta (MN 10) and the Ānāpānasati Sutta (MN 118). The method employs qualitative library research using synchronic, diachronic, and hermeneutic analyses. The findings indicate that the meditative structure centered on sati, observation of vedanā, and observation of citta functions as a systematic mechanism for reducing mental reactivity underlying stress and anxiety, and corresponds to modern psychological concepts such as mindfulness, emotion regulation, and decentering. In conclusion, sutta-based meditation represents a transformative mental process with preventive and curative relevance for modern life and contributes to contemporary mental health literature.